The Relationship of Wudhu with Psychological and Physical Health - Andriyani Andriyani; Masyitoh Chusnan; Nahuda Nahuda; Syahrullah Syahrullah (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2022)
Wudhu is a direct command from Allah SWT which is written in the Qur'an as a way of purification before praying. However, when examined from the shari'ah dimension, the Wudhu procedures taught by the Prophet Muhammad turned out to contain wisdom and secrets hidden in it. Previous studies have proven that performing Wudhu in accordance with the guidance taught by the Prophet SAW can actually provide physical and psychological benefits to humans. This study aims to determine the activity of Wudhu with health. This type of article is a literature review article by reviewing 5 journals regarding the effect of Wudhu on health. This research is descriptive analysis, which is a form of research by describing the data obtained from library sources that have been collected. After a description of the data is then analyzed. Based on the results of previous studies. In this case, health is meant not only physical health such as cleaning bacteria and dirt on body parts exposed to Wudhu water, but Wudhu also relieves emotions when blood pressure increases, in other words, it maintains emotional stability in humans.